Religious Life of the Mototonan Community of the Mentawai Islands (1997-2023) - Tussadiah, Halimah; Zulfa, Zulfa; Erawati, Meri (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This research examines religious life in Matotonan Village, Mentawai Islands, from 1997 to 2023, focusing on the relationship between Muslim and Christian communities and the traditional Arat Sabulungan activities. The Matotonan community exhibits a peaceful, respectful, and cooperative religious life. Tolerance is reflected in collective efforts to build public facilities, social gatherings, and mutual respect in practicing their faiths. Arat Sabulungan activities, known as Liat Pulaggajat, involve all villagers regardless of religion, where Muslims and Christians mingle. Although they do not meet during religious rituals, this does not lead to conflict. Social tolerance is evident in important ceremonies such as births, deaths, and marriages, which involve mutual aid and cooperation. In conclusion, harmonious religious life has been well-established in Matotonan since before 1997, with the community united in social interactions despite religious differences.